Analysis of the Leasing Company's Leadership and Compensation on Employee Performance - Haq Muhammad Hamka Habibie; Moch. Rusli* (Riwayat: Educational Journal of History and Humanities, 2023)
The company has the main source in carrying out its performance, namely man which must be considered carefully, because good Human Resources will create good performance later on the company. A company's human resources can provide optimal results if they are met with appropriate compensation and are also linked to good leadership traits. These two things will at least become benchmarks used by employees to improve personal and company performance. This study discusses the leadership and compensation provided by leasing companies on employee performance. This study aims to determine the relationship between leadership and compensation that will create good employee performance which also impacts on the company's good performance. The method used in this study is a descriptive quantitative method with data collection derived from primary data by giving questionnaires a total of 193 samples from employees of PT Mitsui Leasing Capital Indonesia. In addition to primary data, secondary data is also used to strengthen research originating from journals and articles. The results of the study state that there is a relationship and a positive effect on the relationship between leadership and compensation on employee performance and employee satisfaction at PT Mitsui Leasing Capital Indonesia. Furthermore, there is a positive value between job satisfaction on employee performance. Job satisfaction can provide an indirect media influence on leadership and compensation on employee performance.